(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article describes ways to improve the process of preparing financial reports based on the requirements of international standards, to improve the procedure for planning and conducting financial report audits, and to improve the process of assessing the continuity of activity in financial report audits.